Use of mask in COVID-19 era: absence of evidence is not evidence of absence (Journal of Patan Academy of Health Sciences, 2020)
World Health Organization (WHO) in its interim guidance of 6 April 2020 advises policy makers on the use of masks for healthy people in community settings. The rationale for mask use by healthy person is prevention from COVID-19, when there is risk of exposure, like working in close contact with public, people with comorbidities, where physical distancing cannot be maintained such as travelling in buses, staying in slum areas. Furthermore, WHO says the purpose and reason for mask use should be clear– whether it is to be used for source control (used by infected persons) or prevention of COVID-19 (used by healthy persons).1Centers for Disease Control (CDC) United States of America (USA) updated its advisory on 4 Apr 2020, and recommended everyone (except some) should wear at least a cloth face covering when they have to go out in public. It will protect other people in case you are infected.2,3 This advisory of no strict demand on use of face masks could be possibly due to unavailability of disposable masks.